2019
DOI: 10.1177/0898264319843451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of a Previous Day as a Pathway Between Personality and Healthy Cognitive Aging

Abstract: Objective: To examine the association between Five-Factor Model personality traits and how individuals evaluate a recent day in their lives (yesterday) and whether these evaluations mediate personality and cognitive function over time. Methods: Participants were a subsample from the Health and Retirement Study who completed personality measures in 2008/2010, the day evaluation in 2011, and cognitive tasks in 2012 ( N = 3,454). Results: Lower Neuroticism and Higher Extraversion, Openness, Agreeableness, and Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In contrast, responsibility is linked to better cognition through more time spent engaging in cognitive activities. This pattern is broadly similar to previous research that found that self-reported affect and daily active engagement are mechanisms between the facets and maintaining cognitive function in older adulthood (Sutin et al, 2019). It is important to note, however, that the cognitive tasks and the informant-rated affect and activities were assessed at roughly the same time (the facets were assessed six-to-eight years earlier).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast, responsibility is linked to better cognition through more time spent engaging in cognitive activities. This pattern is broadly similar to previous research that found that self-reported affect and daily active engagement are mechanisms between the facets and maintaining cognitive function in older adulthood (Sutin et al, 2019). It is important to note, however, that the cognitive tasks and the informant-rated affect and activities were assessed at roughly the same time (the facets were assessed six-to-eight years earlier).…”
Section: Discussionsupporting
confidence: 87%
“…An individual's daily affect and activities may be mechanisms that support healthier cognitive aging. Individuals who experience less negative affect (Korthauer et al, 2018) and those involved in more engaging activities (Sutin et al, 2019) tend to maintain their cognitive function in older adulthood. Previous research has shown that individuals high in conscientiousness tend to experience more positive affect and less negative affect on average (Fayard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we found no significant association between meditation practice and self-esteem in each of the two models. Although some earlier studies found positive correlations between mindfulness and self-esteem, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] others did not. 48,49 This negative finding in our study may be due to a wide variety of meditation practice techniques, a long gap between survey waves, categorizing all frequencies of practice in the same group, or the lack of a long-term effect for meditation on certain psychological states and cognitive activities.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, part of the definition of conscientiousness includes a tendency to be responsible to others that is inherently interpersonal. A growing literature indicates that interpersonal facets, specifically responsibility and dutifulness, are associated with better cognitive health, from performance on cognitive tasks (Sutin, Stephan, Aschwanden, et al, 2020) to risk of Alzheimer’s disease (Terracciano et al, 2014) and dementia (Sutin et al, 2018; Terracciano et al, 2022). The results of the current sample are consistent with this growing literature and highlight the importance of this interpersonal facet to cognitive health.…”
Section: Discussionmentioning
confidence: 99%